Questioning the Chinese model : oppositional political novels in early twenty-first century China - Yu, Zhansui (University of Toronto Press, 2023)
"This book examines how political novels produced in 21st century China challenge the fundamental principles of the Chinese one-Party state and question the morality and political legitimacy of the Chinese model. Based on close readings of five representative oppositional Chinese political novels, the study examines the sociopolitical connotations and epistemological values of these novels in the broad context of modern Chinese intellectual history and contemporary Chinese politics and society. The book attempts to draw a sketch of the social, political, and intellectual landscape of present-day China, and investigates the dialectic relationship between art and politics in the Chinese context, the mechanisms and dynamics of censorship and counter-censorship in the age of the Internet and commercialization, and the ideological limitations of oppositional Chinese political novels."--